France Marolt’s Endeavours to Sound Document Folk Music - Drago Kunej (Muzikološki Zbornik, 2020)
The paper presents France Marolt’s endeavours spanning many years to acquire the recording devices that he planned to use for documenting folk music in the field, as well as for his research work and various forms of educational and cultural activities. The main focus is on researching the circumstances in which sound recordings on gramophone records were made in collaboration with Radio Ljubljana, and on the first sound collection of the Institute of Ethnomusicology ZRC SAZU, which consisted of these records. The records have a special documentary value and, combined with archival documents, convey Marolt’s view of folk music.